Prospective study of the tourist sector in La Pampa, Argentina (Huellas, 2020)
Nowadays, planning and management of tourist potentials of the territories constitute an essential requirement for the development of the activity, as they guarantee the proper integration of tourism into the economy, society and local culture. This research paper considers the tourism activity as one more variable of analysis of a territory, a social practice that constitutes and is part of the socioeconomic and cultural dynamic of the space. The idea of carrying out a Prospective Study of the sector results from the awareness of the importance of tourism for La Pampa. The main objective is to analyze the current situation of the activity and the possibilities for development with special emphasis on the cultural, patrimonial and natural attractions. Among the specific objectives, this study seeks to know the situation of tourism in La Pampa’s territory from the identification of different sectors and institutions linked to such activity; to identify opportunities and risks that the province of La Pampa presents for the development of this activity and to analyze the role of provincial municipalities in the future tourist demand with reference to the elements from the offer in the coming years.
Keywords: Tourism; Planning; Prospective; Development